Elucidating Article 45.6 of the International Code of Zoological Nomenclature: A dichotomous key for the determination of subspecific or infrasubspecific rank - Lingafelter, Steven W.; Nearns, Eugenio H. (Zootaxa, 2013)
We present an overview of the difficulties sometimes encountered when determining whether a published name following a binomen is available or infrasubspecific and unavailable, following Article 45.6 of the International Code of Zoological Nomenclature (ICZN, 1999). We propose a dichotomous key that facilitates this determination and as a preferable method, given the convoluted and subordinate discussion, exceptions, and qualifications laid out in ICZN (1999: 49–50). Examples and citations are provided for each case one can encounter while making this assessment of availability status of names following the binomen.